TECHNICAL UNIVERSITY AS A MULTILEVEL EDUCATIONAL COMPLEX: FROM THE EXPERIENCE OF EDUCATION OF YOUNG STUDENTS - S. V. Sergeeva; O. A. Voskrekasenko (Образование и наука)
The purpose of the article is summarizing the experience and determination of the main vectors of educational work organization and implementation in a technical university as a multi-level educational complex (MEC).Methods. Theoretical methods such as the analysis of scientific literature, the synthesis of the main concepts and approaches to the problem under consideration, the generalization of experience are used.The results and scientific novelty. A long-term positive experience of educational system constructing in Penza State Technological University as a multi-level educational complex is presented. On its basis the main vectors of the educational work organization and implementation in a modern multi-level educational organization of a technical profile are determined: the formation of social competence of students, pedagogical support of their adaptation and professional selfdetermination, the student government development. The complex of the programs developed by the authors to educate young students in a technical university as a multi-level educational complex is characterized. Their realization involves a phased implementation of the initial diagnosis, constructive, transformative, evaluative and productive activities. The necessity of the organization and implementation of additional psychological and pedagogical training of teachers who do not have the basic pedagogical education as a condition for the effective implementation of the programs developed and put into educational practice in a multi-level educational organization of a technical profile is determined.Practical significance. The presented materials can be used in the educational practice of multi-level educational complexes of a technical profile as well as in other educational institutions of vocational education.